Influence of cardiovascular health behaviors and factors on the incidence of hypertension in young and middle-aged population - Yan Lei; Li Ying; Wang Jiangang; Yang Pingting (生物医学转化)
Objective Aims to investigate the effects of these ideal cardiovascular health behaviors and factors on the incidence of hypertension in young and middle-aged populations. Methods A cohort of 5 372 employed individuals who underwent annual health examinations at The Third Xiangya Hospital of Central South University between 2015 and 2016 was selected for the study. The incidence of hypertension was monitored, and a multivariate Cox proportional hazards regression model was applied. After adjusting for relevant factors, the risks of hypertension and cumulative effects were compared among groups with different ideal cardiovascular health behaviors and factors. Results A total of 4 883 subjects were included in the analysis, with a mean age of (37.80±9.92) years. The average follow-up period was 5.33 years, during which 1 048 new cases of hypertension were identified, resulting in a cumulative incidence rate of 21.46%. After adjusting for relevant risk factors, the risk of developing hypertension was reduced by 21% (HR=0.79, 95% CI 0.69-0.92) for non-smokers, 34% (HR=0.66, 95% CI 0.58-0.75) for those with ideal body weight, 33% (HR= 0.67, 95% CI 0.58-0.77) for regular exercisers, 80% (HR=0.20, 95% CI 0.17-0.25) for those with ideal blood pressure, and 12% (HR=0.88, 95%CI 0.77-0.99) for those with ideal cholesterol levels compared to smokers, those with nonideal body weight, non-regular exercisers, those with non-ideal blood pressure, and those with non-ideal cholesterol levels. The proportions of study subjects exhibiting 0-2, 3, 4, 5, and 6-7 ideal cardiovascular health behaviors and factors were 14.64%, 18.62%, 25.76%, 28.40%, and 12.57%, respectively, with corresponding cumulative incidence rates of hypertension at 50.35%, 32.67%, 20.83%, 6.99%, and 5.21%. Compared to individuals with 0-2 ideal cardiovascular health behaviors and factors, the risks of developing new hypertension were reduced by 33% (HR=0.67, 95% CI 0.58-0.79), 57% (HR=0.43, 95% CI 0.36-0.51), 82% (HR=0.18, 95% CI 0.14-0.23), and 85% (HR=0.15, 95% CI 0.10-0.21) for those with 3, 4, 5, and 6-7 ideal behaviors and factors, respectively. Conclusion Ideal cardiovascular health behaviors and other factors were identified as protective against the occurrence of hypertension.